DNA barcode of Enggano hill myna, Gracula religiosa enganensis (Aves: Sturnidae) based on mitochondrial DNA cytochrome oxidase subunit I - JARULIS JARULIS; CHOIRUL MUSLIM; SANTI NURUL KAMILAH; AHMAT FAKHRI UTAMA; DEBY PERMANA; MELISA MAYANG SARI; ALEX HADI PRAYITNO; IZUL MIFTAKHUL JANNAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Jarulis, Muslim C, Kamilah SN, Utama AF, Permana D, Sari MM, Prayitno AH, Jannah IM. 2021. DNA barcode of Enggano hill myna, Gracula religiosa enganensis (Aves: Sturnidae) based on mitochondrial DNA cytochrome oxidase subunit I. Biodiversitas 22: 1635-1643. The sharp decline of the Enggano hill myna population due to illegal trading and habitat degradation needs to be our concern to prevent this bird from extinction. Taxonomically, Enggano hill myna is referred to as a sub-species, but this has not been confirmed by genetic data. We have sequenced seventeen Enggano hill myna mitochondrial DNA COI genes to describe their genetic identity (barcode), genetic distances, and phylogeny. DNA genome from seventeen blood samples was isolated with DNeasy® Blood and Tissue Kit Qiagen, while PCR amplification was performed using a pair primers, namely COIGRF (5'-TTCTGATTCTTTGGCCATCC-3') and COIGRR (5'-GTTGGAAGGCTTTGCGTTTA-3'). We used Clustal W alignment in MEGA 10.2.2 software to search single nucleotide polymorphisms. Genetic distance was analyzed by using the Kimura 2-parameter, and the phylogenetic tree was reconstructed with Neighbor-Joining models. We found 98.60% conservative sites, 0.69% parsimony sites, and 0.83% singleton sites from the 716 bp sequence. The highest nucleotide composition was cytosine (32.20%), and the lowest was guanine (16.80%), followed by 49% GC content. Seven SNP sites were found in 716 bp COI gene sequences of seventeen individuals. The genetic distance between Enggano hill myna individuals was ranged from 0.0-0.8%, and all Enggano hill myna individuals separated from Chinese and Indian populations in the phylogenetic tree with a genetic distance of 0.9% and 1.1%. Our data suggest that the Enggano hill myna population is still classified as a sub-species. The COI gene sequences that we found can be used to quickly identify this species and are also important to prevent illegal trading in Indonesia.